Monetary Integration in East Asia: Why Does it Take so Long? (International Journal of Banking and Finance, 2009)
The launch of the economic and monetary union in Europe and the 1997 financial crisis that underscored the disadvantages of currently employed exchange rate regimes raised questions about the feasibility of a similar monetary unification project for East Asia. Being one of the most dynamically growing regions in the world, East Asia has the potential for a successful implementation of a monetary union. The paper examines why, despite substantial political emphasis being placed on the issue of monetary integration, the progress to date has been slower than could be expected. The major finding is that, although East Asia may actually benefit from establishing its monetary union in the long run, a specific political culture that prevails in the region and misconceptions about the sequencing of the process prevent the East Asian monetary union from materialising. Possible short and mid-term policy solutions follow.